Geology defines microbiome structure and composition in nunataks and valleys of the Sør Rondane Mountains, East Antarctica - Savaglia, Valentina; Lambrechts, Sam; Tytgat, Bjorn; Vanhellemont, Quinten; Elster, Josef; Willems, Anne; Wilmotte, Annick; Verleyen, Elie; Vyverman, Wim (Frontiers in Microbiology, 2024)
Understanding the relation between terrestrial microorganisms and edaphic factors in the Antarctic can provide insights into their potential response to environmental changes. Here we examined the composition of bacterial and micro-eukaryotic communities using amplicon sequencing of rRNA genes in 105 soil samples from the Sør Rondane Mountains (East Antarctica), differing in bedrock or substrate type and associated physicochemical conditions. Although the two most widespread taxa (Acidobacteriota and Chlorophyta) were relatively abundant in each sample, multivariate analysis and cooccurrence networks revealed pronounced differences in community structure depending on substrate type. In moraine substrates, Actinomycetota and Cercozoa were the most abundant bacterial and eukaryotic phyla, whereas on gneiss, granite and marble substrates, Cyanobacteriota and Metazoa were the dominant bacterial and eukaryotic taxa. However, at lower taxonomic level, a distinct differentiation was observed within the Cyanobacteriota phylum depending on substrate type, with granite being dominated by the Nostocaceae family and marble by the Chroococcidiopsaceae family. Surprisingly, metazoans were relatively abundant according to the 18S rRNA dataset, even in samples from the most arid sites, such as moraines in Austkampane and Widerøefjellet ('Dry Valley'). Overall, our study shows that different substrate types support distinct microbial communities, and that mineral substrate diversity is a major determinant of terrestrial microbial diversity in inland Antarctic nunataks and valleys.